Analisis Kesalahan Berbahasa Pada Teks Prosedur Kelas IX SMPIT Darul Muta’allimin - Ajeng Raya Vidia; Yayu Sopa Ikmali Rijki; Siti Elinda Nur Pebriantini; Ai Siti Nurjamilah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to describe and analyze language errors in 5 procedural texts produced by SMPIT Darul Muta'allimin students. The research method used is descriptive qualitative with data collection techniques in the form of documents. The results obtained contained language errors in the categories of morphology, phonology, spelling and signs which included: 2 morphological errors, 4 phonological errors, and 1 spelling and punctuation error.